Distribution of heavy metals in bottom sediments of water-houses after vermicultivation - Тимчий, К. І.; Сідашенко, О. І.; Бабченко, А. В.; Сметанін, В. Т. (Problems of Environmental Biotechnology, 2020)
The regularities of the distribution of migration and accumulation of heavy metals in the samples of bottom sediments biotransformed by vermiculture of the genus Eisenia are studied. The changes in the mobility coefficient of heavy metals: Mg, Ni, Zn, Cu, Pb, Cd in biotransformed substrates are determined. The positive effect of biotransformation by vemiculture of various groups of the genus Eisenia on the increase in the mobility coefficient of heavy metals, in particular Cu, by 1.8 times, Pb, by 2 times, Cd, by 1.09 times, and Ni, by 1.55 times, was experimentally proved. compared to control.